Analysis of Proteins of Virus Containing Suspensions, Stored under Moderately Low Temperatures - Stegniy, M. Yu.; Semenchenko, A. Yu. (Problems of Cryobiology and Cryomedicine, 2004)
The authors have performed the analysis of proteins of non-purified suspensions of cattle diarrhea virus (DV), â€œOregon C-24 Vâ€ strain, subjected to freezing with a further storage at -18, -30Â°Ð¡ from 20 days to 10 years. At the same time there were revealed both the decrease of infectious activity and the degradation of virus-containing suspensions proteins, stored for a long time at moderately low temperature.